Analisa Optimasi Rute Pengiriman Pre Order (PO) di Jakarta Zone pada PT. X - Felix Valentino; I Gede Agus Widyadana (Jurnal Titra, 2018)
PT.X is a company that working on Fast Moving Consumer Goods (FMCG) section. This company has more than 100 selling area that located in all over Indonesia. There are various selling system or distribution system in this company and one of them is Pre Order system (PO). The vehicle types that used for delivery on this system are blind van, Colt Diesel Engkel (CDE), and Cold Diesel Double (CDD). The purpose of this research is to discovered route optimitation so it can shows how many vehicles are needed for the delivery. It also can decrease the operational cost for the delivery. This route optimitation simulation is based on the existing route but it had been optimized with arranging the delivery using the Nearest Neighbor Insertion (NNI) concept where the delivery route will be using the shortest route. This PO delivery system also using the combination of Vehicle Routing Problem with Time Windows (VRPTW), Vehicle Routing Problem with Heterogenouse Fleet of Vehicle (VRPHFV), and Vehicle Routing Problme with Multiple Trips (VRPMT).The result of this simulation is the total number of vehicles that can be decreased in one week are 34 unit. In Bogor, Ciracas and Pulo Gadung, 1 unit of vehicle can be removed for Senin until Thursday (1*4*3=12). In Sunter, there are 3 unit of vehicles that can be removed for Monday until Thursday (3*4) and lastly in Tangerang there are 2 unit of vehicles that can be removed for Monday untul Friday (2*5=10). The distances that should be taken are decreased from 9,604 km to 8,028 km with total duration 1372,01 hours when it actually should be taking 1484,3 hours. The reducing of distance and time become a great additional benefit for the company because the company can save more fuel that can also reduce the polution of CO2. For the saving of the cost in this simulation is from Rp. 948,017,052.66 become Rp.797,589,503.62.